Dari Kata ke Kesadaran: Transformasi Pemikiran Manusia di Era Digital dalam Perspektif Filsafat Bahasa - Muhammad Faishal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the transformation of human consciousness through words in the digital era with a philosophy of language approach. The main focus is on how words spread through social media affect the mindset, attitude and consciousness of individuals and society. The method used is explorative qualitative with content analysis on various digital sources and related literature. The results show that words not only shape opinions and emotional responses, but also play a role in building critical consciousness through the dynamic context of language use. This research reveals the concept of “digital consciousness transformation” as a phenomenon in which language becomes the main instrument in shaping social and cultural realities in the digital media era. Thus, an in-depth understanding of the power of words in the digital context can encourage wiser and more constructive communication, as well as enrich the study of the philosophy of language in the face of the development of information technology.